Comparative cervical profiles of adult and under-18 front-row rugby players: implications for playing policy. Issue 5 (5th May 2014) - Hamilton, D F; Gatherer, D; Robson, J; Graham, N; Rennie, N; MacLean, J G B; Simpson, A H R W
Abstract : Objective: To compare the cervical isometric strength, fatigue endurance and range of motion of adult and under-18 age-grade front-row rugby players to inform the development of a safe age group policy with particular reference to scrummaging. Design: Cross-sectional cohort study. Setting: 'Field testing' at Murrayfield stadium. Participants: 30 high-performance under-18 players and 22 adult front-row rugby players. Outcome measures: Isometric neck strength, height, weight and grip strength. Results: Youth players demonstrated the same height and grip strength as the adult players; however, the adults were significantly heavier and demonstrated substantially greater isometric strength (p<0.001). Only two of the 'elite' younger players could match the adult mean cervical isometric strength value. In contrast to school age players in general, grip strength was poorly associated with neck strength (r=0.2) in front-row players; instead, player weight (r=0.4) and the number of years' experience of playing in the front row (r=0.5) were the only relevant factors in multivariate modelling of cervical strength (R 2 =0.3). Conclusions: Extreme forces are generated between opposing front rows in the scrum and avoidance of mismatch is important if the risk of injury is to be minimised. Although elite youth front-row rugby players demonstrate the same peripheral strength as their adult counterparts on grip testing, the adults demonstrate significantly greater cervical strength. If older youths and adults are to play together, such findings have to be noted in the development of age group policies with particular reference to the scrum.